THE EFFECT OF THE USE OF SPECIAL ORTODONTIC DENTAL ATTITUDES TOWARDS DENTAL AND MOUTH CLEANER STATUS OF HIGH ORTHODONTIC USERS IN BANDA ACEH 3 STATE VOCATIONAL SCHOOL STUDENTS - wirza wirza; Ratna Wilis (Poltekkes Kemenkes Jambi, 2019)
Good oral hygiene is a challenge for orthodontic patients because food easily becomes trapped around brackets and under archives so that it is a barrier during brushing. Mechanical tooth cleaning is the most effective effort to prevent plaque from occurring, one of which is by brushing teeth. Although a toothbrush is the most effective mechanical tool for cleaning plaque, the effectiveness of brushing teeth also depends on the shape of the toothbrush, the long frequency of brushing teeth and a good method for everyone to use. This study aims to determine the effect of using orthodontic toothbrushes on the status of oral and dental hygiene in fixed orthodontic users in students of SMK Negeri 3 Banda Aceh. This type of research is quasi experimental. The subjects in this study were all students who used fixed orthodontics 30 people, then divided into two groups, the intervention group consisted of 15 people given intervention (brushing using orthodontic toothbrushes) and the control group consisted of 15 people who were not given intervention (brushing teeth using a conventional toothbrush). The sampling technique in this study was purposive sampling Analysis of the results of data (quantitative) in this study using; using the non parametric t test (Wilcoxon) and Mann Whitney. The results showed that there were differences in the mean values ​​of dental and oral hygiene status (PHP-M index) in the treatment group and the control group which were statistically significant (p <0.05) before and after brushing using conventional orthodontic and toothbrush toothbrushes on fixed orthodontic users in students of SMK Negeri 3 Banda Aceh. There was a significant difference in the PHP-M Index after the intervention (post-test) between the treatment groups (brushing teeth using orthodontic toothbrushes) and the control group (brushing using conventional toothbrushes), this was shown statistically p <0.05) . It is recommended that you always maintain oral hygiene so that the teeth and gum tissues remain healthy by brushing your teeth, at least twice a day, namely after breakfast, and the night before